Le Labyrintho de comercio terrestre y naval de Juan de Hevia Bolaño et le droit maritime - Margarita Serna Vallejo (Clio@Themis)
The III Book of the Labyrintho de comercio terrestre y naval by Hevia Bolaño is an expression of the transnational legal history of maritime law of the Hispanic Monarchy. The author recasts the maritime law created by sailors on the European coasts since the Middle Ages, with the maritime law established by the Monarchy to order trade with the Indies under a monopoly regime. Understanding it requires linking the book with the « process of establishing the law » made by the Monarchy and with the situation of the doctrine on mercantile and maritime law in the early sixteenth century.